Prediction and bioactivity of small-molecule antimicrobial peptides from Protaetia brevitarsis Lewis larvae - Fu, Qian; Cao, Dengtian; Sun, Jing; Liu, Xinbo; Li, Haitao; Shu, Changlong; Liu, Rongmei (Frontiers in Microbiology, 2023)
Antimicrobial peptides (AMPs) are widely recognized as promising natural antimicrobial agents. Insects, as the group of animals with the largest population, have great potential as a source of AMPs. Thus, it is worthwhile to investigate potential novel AMPs from Protaetia brevitarsis Lewis larvae, which is a saprophagous pest prevalent in China. In this study, comparing the whole-genome sequence of Protaetia brevitarsis Lewis larvae with the Antimicrobial Peptide Database (APD3) led to the identification of nine peptide templates that were potentially AMPs. Next, based on the peptide templates, 16 truncated sequences were predicted to the AMPs by bioinformatics software and then underwent structural and physicochemical property analysis. Thereafter, candidate small-molecule AMPs were artificially synthesized and their minimal inhibitory concentration (MIC) values were assessed. A candidate peptide, designated FD10, exhibited strong antimicrobial activity against both bacteria and fungi comprising Escherichia coli (MIC: 8 μg/mL), Pseudomonas aeruginosa (MIC: 8 μg/mL), Bacillus thuringiensis (MIC: 8 μg/mL), Staphylococcus aureus (MIC: 16 μg/mL), and Candida albicans (MIC: 16 μg/mL). Additionally, two other candidate peptides, designated FD12 and FD15, exhibited antimicrobial activity against both E. coli (MIC: both 32 μg/mL) and S. aureus (MIC: both 16 μg/mL). Moreover, FD10, FD12, and FD15 killed almost all E. coli and S. aureus cells within 1 h, and the hemolytic effect of FD10 (0.31%) and FD12 (0.40%) was lower than that of ampicillin (0.52%). These findings indicate that FD12, FD15, and especially FD10 are promising AMPs for therapeutic application. This study promoted the development of antibacterial drugs and provided a theoretical basis for promoting the practical application of antimicrobial peptides in the Protaetia brevitarsis Lewis larvae.